(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
The upsurge of multi-drug resistance by microbes is at alarming rate and poses serious challenges in the field of medical and pharmaceutical industries. This study was aimed to determine the active components and assess the antibacterial potency of methanolic leaf extract of Boswellia dalzielii. The plant specimen was collected, identified, prepared and cold macerated using 95% of methanol as solvent. The resulted crude extract was further assayed for anti-bacterial potency; adopting agar well diffusion protocol against some selected human pathogenic isolates viz S. aureus, S. pyogenes, B. Subtilis, Corynebact. Spp. K. pneumoniae, S. typhi,P. aeruginosa and E. coli. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined using the standard protocol of microdilution assay. The antimicrobial assay of the crude extract showcased that B. dalzielii leaf is susceptible against all the tested pathogens by exhibiting significant degrees of inhibition zone of diameter (0.25±0.26to 27.16±0.76 mm). The positive control (ciprofloxacin) showed superior activity against the tested isolates (27.06±0.35 to31.03±0.64 mm). The MIC/MBC was observed at 25.0 to 6.25 mg/mL and 25.0 to 12.5 mg/mL against bacterial studied. S. aureus is the most susceptible pathogen with MIC/MBC values at 6.25/12.5 mg/ml respectively while S. Pyogene, B. subtilis, P. aeruginosa were inhibitory at 12.5 mg/ml and bactericidal at 25mg/ml. Corynebact. Spp. and K. pneumoniae had the moderate MIC/MBC at 25mg/ml. The phytochemical analysis revealed the presence of alkaloids, flavonoids, cardiac glycosides, saponins, steroids, terpenoids, resins, tannins and carbohydrates. This study showed that B. dalzielii leaf has a strong antibacterial activity against Gram +ve and Gram -ve bacteria tested; this provides a scientific justification to the traditional healers for the utilization of the plant in the management of different ailments caused by the tested pathogens.